Melawan Cyberbullying: Membangun Kesadaran Kemanusiaan dalam Etika Bermedia Sosial Perspektif Al-Qur’an - Abd. Basid; Wildana Rahmah (Studia Quranika, 2023)
Social media is an inseparable part of today’s global society. It becomes a very effective instrument in shaping a dynamic society. The convenience it offers makes people more responsible for complete information. There, people find many things and learn in many ways as well. Its presence facilitates all forms of social interaction in the virtual world. However, on the one hand, this convenience turned out to be an anomaly, including the rampant phenomenon of cyberbullying, which is like a form of virtual world crime, even if only in verbal form, such as bullying, body shaming, toxic people, cancel culture, hate-speech, and fake-news. In the Qur’an, this phenomenon’s characteristics have existed and been discussed. However, in responding to this phenomenon, few still present religion (the Qur’an) as a solution perspective. By applying qualitative-descriptive methods and thematic approaches, this study tries to present relevant verses with asbab al-nuzul, which will later be able to find solutions to the cyberbullying phenomenon so that awareness and ethics in social media can be created. In the end, this study concludes that to build human awareness of social media ethics so that cyberbullying does not occur, the Qur’an states the importance of tabayun and qaulan sadida